Teaching Procedures and Skills in Medical Schools: Gaps, Weakness, and Challenges - Mohamed D. Awadalla Gismalla (Sudan Journal of Medical Sciences)
There is deficiency and gaps among medical graduates in performing certain procedures and skills. Till recent years, some school used an apprenticeship model for teaching procedures. The way of teaching skills should be revised and reinforced. Medical schools showed adopt formal curricula based training for teaching procedure. In this letter, we would like to highlight the challenges and weakness in teaching procedure for undergraduates medical students.